Microalgae-based hydrogel drug delivery system for treatment of gouty arthritis with alleviated colchicine side effects - Xiaoyang Liu; Jia Dong; Zhongshu Wu; Jiarong Cui; Yixin Zheng; Min Zhou (Bioactive Materials)
Gouty arthritis (GA) is a type of inflammatory arthritis caused by the deposition of monosodium urate crystals. Current clinical therapies fail to simultaneously reduce uric acid (UA) levels and alleviate inflammation. Previous studies have demonstrated that Euglena (Eug) polysaccharides can effectively adsorb UA. Colchicine (Col), the most prescribed medication for GA, exhibits anti-inflammatory effects but is associated with significant side effects. Here, we developed an oral microalgae-based hydrogel system (Eug-Col@Fucar) utilizing Fucar to load the Eug-Col complex, aiming to synergistically reduce UA levels and alleviate inflammation in GA treatment. Eug-Col@Fucar regulated release characteristics and enhanced intestinal retention, thereby mitigating the side effects associated with oral Col. The oral administration of Eug-Col@Fucar could inhibit the progression of GA by eliminating reactive oxygen species, reprogramming the inflammatory microenvironment to promote cell polarization towards M2-like anti-inflammatory cells, inhibiting the NLRP3-IL-1β pathway, and reducing the expression of pro-inflammatory factors. Additionally, Eug-Col@Fucar improved bile acid metabolism in vivo, alleviating the intestinal-hepatic circulation damage caused by Col. This study presents a safe, simple, and highly effective treatment strategy for managing GA and alleviating the gastrointestinal side effects that arise from the long-term administration of Col, demonstrating clinical practicability.